Perbandingan Hasil Belajar Biologi melalui Model Pembelajaran Student Team Achievement Division dan Jigsaw pada siswa Kelas XI SMA Negeri 1 Sangatta Utara, Kalimantan Timur : Comparison of Biology Learning Outcomes through Student Team Achievement Division and Jigsaw Learning Models in Class XI North Sangatta 1 High School students - Fajrin Fajrin; Elsje Theodora Maasawet; Sonja V.T Lumowa (BIODIK, 2019)
This research is motivated by the problem of low learning outcomes in Biology subjects due to the lack of use of varied learning models. This study aims to describe the comparison of Biology learning outcomes through STAD learning model, and Jigsaw on students conducted in April to May 2017. Data collection in this research is obtained from the test method. The data obtained from the test method were analyzed by descriptive and inferential statistical techniques (t-test), using SPSS version 23. The study showed, (1) there was comparison of learning outcomes among students who studied STAD learning model with conventional model. Based on statistical results obtained sig value. 0,000 <0.05; (2) there is comparison of learning result among students learning Jigsaw learning model with conventional model, this result is in accordance with statistical result where sig.0,000 <0,05. Keywords: Student Team Achievement Division (STAD) Model, Jigsaw Model. Abstrack.Penelitian ini dilatarbelakangi oleh masalah yaitu rendahnya hasil belajar pada mata pelajaran Biologi dikarenakan masih kurangnya penggunaan model pembelajaran yang bervariasi. Penelitian ini bertujuan untuk mendeskripsikan perbandingan hasil belajar Biologi melalui model pembelajaran STAD dan Jigsaw, pada siswa yang dilaksanakan pada Bulan April sampai Mei 2017. Pengumpulan data dalam penelitian ini didapatkan dari metode tes. Data yang didapatkan dari metode tes dianalisis dengan teknik analisis deskriptif dan statistif inferensial (uji-t), dengan menggunakan SPSS versi 23. Penelitian menunjukkan, (1) ada perbandingan hasil belajar antar siswa yang belajar model pembelajaran STAD dengan model konvensional. Berdasarkan hasil statistik diperoleh nilai sig. 0,000 < 0,05; (2) ada pebandingan hasil belajar antar siswa yang belajar model pembelajaran Jigsaw dengan model konvensional, hasil ini sesuai dengan hasil statistik dimana nilai sig.0,000 < 0,05. Kata kunci: Model Student Team Achievement Division (STAD), Model Jigsaw.